Environmental and Metabolic Sensors That Control T Cell Biology - Ramsay, George; Cantrell, Doreen (Frontiers in Immunology, 2015)
The T lymphocyte response to pathogens is shaped by the microenvironment. Environmental sensors in T cells include the nutrient-sensing serine/threonine kinases, adenosine monophosphate-activated protein kinase and mammalian target of rapamycin complex 1. Other environmental sensors are transcription factors such as hypoxia-inducible factor-1 and the aryl hydrocarbon receptor. The present review explores the molecular basis for the impact of environmental signals on the differentiation of conventional T cell receptor αβ T cells and how the T cell response to immune stimuli can coordinate the T cell response to environmental cues.